Kerr nonlinear coupler and entanglement induced by broadband laser light - Doan, Quoc Khoa; Cao, Long Van; Chu, Van Lanh; Nguyen, Thanh Vinh; Tran, Thi Hai; Ha, Kim Quy; Nguyen, Thi Hong Sang (Photonics Letters of Poland, 2016)
We consider a model of Kerr-like nonlinear coupler linearly excited by a external classical field involving coherent part and white noise and solved a set of coupled stochastic integro-differential equations, deriving exactly analytical formulae for the probability amplitudes of n-photon Fock states. As a consequence, this nonlinear coupler deliberated behaves as a two-qubit system. The effects of dissipation on entanglement of formation parameterised by concurrence are also analyzed and compare these results with that obtained previously in the literature. As a interesting result, initially for a period of time the entanglement is enlarged when the chaotic parameter increases. Full Text: PDF References A. Einstein, B. Podolski, N. Rosen, "Can Quantum-Mechanical Description of Physical Reality Be Considered Complete?", Phys. Rev. 47, 777 (1935). CrossRef A. Miranowicz, W. Leoński, "Two-mode optical state truncation and generation of maximally entangled states in pumped nonlinear couplers", J. Phys. B 39, 1683 (2006). CrossRef T.D. Nguyen, W. Leoński, V. Cao Long, "Computer Simulation of Two-Mode Nonlinear Quantum Scissors", Comput. Method. Sci. Tech. 19, 175 (2013). CrossRef N. Korolkova, J. Peřina, "Quantum statistics and dynamics of Kerr nonlinear couplers", Opt. Commun. 136, 135 (1997). CrossRef A. Kowalewska-Kudłaszyk, W. Leoński, "Finite-dimensional states and entanglement generation for a nonlinear coupler", Phys. Rev. A 73, 042318 (2006). CrossRef A. Kowalewska-Kudłaszyk, W. Leoński, T.D. Nguyen, V. Cao Long, "Kicked nonlinear quantum scissors and entanglement generation", Phys. Scr. T 160, 014023 (2014). CrossRef K. Doan Quoc, V. Cao Long, W. Leoński, "Electromagnetically induced transparency for Λ-like systems with a structured continuum and broad-band coupling laser", Phys. Scr. T 147, 014008 (2012). CrossRef K. Doan Quoc, V. Cao Long, W. Leoński, "A broad-band laser-driven double Fano system—photoelectron spectra", Phys. Scr. 86, 045301 (2012). CrossRef K. Doan Quoc, V. Cao Long, L. Chu Van, P. Huynh Vinh, "Electromagnetically induced transparency for Λ-like systems with degenerate autoionizing levels and a broadband coupling laser", Optica Applicata 46, 93 (2016). CrossRef W. Leoński, A. Miranowicz, "Kerr nonlinear coupler and entanglement", J. Opt. B 6, S37 (2004). CrossRef K. Doan Quoc, V. Cao Long, to be Published. W. Leoński, "Finite-dimensional coherent-state generation and quantum-optical nonlinear oscillator models", Phys. Rev. A 55, 3874 (1997). CrossRef